VLSI: Technology,Design & Basic of Microelectronics - Singh,R.K (S.K.Kataria, 2007)
VLSI: Technology,Design & Basic of Microelectronics / Singh,R.K.. -- Delhi: S.K.Kataria, 2007 621.395 Si617 No. of Copies : 1